The social economy in the digital era: A perspective on community enterprises in a developing economy - Jangjarat, Kris; Kraiwanit, Tanpat; Satityapong, Narest; Sonsuphap, Rattaphong; Phaksipaeng, Itsaree (Journal of Social Economics Research, 2023)
Daily life is inextricably linked to the economy, especially when it comes to eating well and saving money, which can be seen as creating favourable economic conditions for both the individual and the household. The social economy is a critical engine for economic restructuring in the digital economy, as well as for increasing societal and economic resilience, fairness and sustainability. This study employed a quantitative approach to investigate the factors that influence the social economy in the community enterprise sector in developing countries. An online questionnaire was used to collect data from 619 participants in Thailand recruited through accidental sampling. Multiple regression analysis was used to analyse the data. The findings revealed that the social economy can be influenced by demographic factors such as age, residence and technological readiness, as well as online communication platforms such as Instagram, Pinterest, Facebook and blogs. Career opportunities should be encouraged by helping groups of people, gathered based on common interests, to establish businesses that endorse community and social activities, thereby strengthening the community and beyond. People of diverse ages should be included to broaden the participation in activities.